Monitoring training activity during gait-related balance exercise in individuals with Parkinson's disease: a proof-of-concept-study. Issue 1 (December 2017) - Conradsson, David; Nero, Håkan; Löfgren, Niklas; Hagströmer, Maria; Franzén, Erika
Abstract Background Despite the benefits of balance exercise in clinical populations, balance training programs tend to be poorly described, which in turn makes it difficult to evaluate important training components and compare between programs. However, the use of wearable sensors may have the potential to monitor certain elements of balance training. Therefore, this study aimed to investigate the feasibility of using wearable sensors to provide objective indicators of the levels and progression of training activity during gait-related balance exercise in individuals with Parkinson's disease. Methods Ten individuals with Parkinson's disease participated in 10 weeks of group training (three sessions/week) addressing highly-challenging balance exercises. The training program was designed to be progressive by gradually increasing the amount of gait-related balance exercise exercises (e.g. walking) and time spent dual-tasking throughout the intervention period. Accelerometers (Actigraph GT3X+) were used to measure volume (number of steps/session) and intensity (time spent walking >1.0 m/s) of dynamic training activity. Training activity was also expressed in relation to the participants' total daily volume of physical activity prior to the training period (i.e. number of steps during training/the number of steps per day). Feasibility encompassed the adequacy of data sampling, the output of accelerometer data and the participants' perception of the level of difficulty of training. Results Training activity data were successfully obtained in 98% of the training sessions (n = 256) and data sampling did not interfere with training. Reflecting the progressive features of this intervention, training activity increased throughout the program, and corresponded to a high level of the participants' daily activity (28–43%). In line with the accelerometer data, a majority of the participants (n = 8) perceived the training as challenging. Conclusions The findings of this proof-of-concept study support the feasibility of applying wearable sensors in clinical settings to gain objective informative measures of gait-related balance exercise in individuals with Parkinson's disease. Still, this activity monitoring approach needs to be further validated in other populations and programs including gait-related balance exercises. Trial registration NCT01417598, 15th August 2011.